(untitled) (Journal of Parents and Teachers, 2022)
Making decisions in relation to technology and digital competence, and doing so in a coherent way, involves first establishing a sufficiently solid strategic framework that allows us to specify and operationalize a set of reflections and documents that guide our steps. This concretion must, on the other hand, be born from deep pedagogical and educational reflection and knowledge of our reality and our context. In this article we propose a possible model to prepare the ground so that the decisions to be made are based on an argument that stems from our mission and our educational project.